Effects of the incorporation of alpha-tocopherol as antioxidant on biological and physicochemical properties of calcium hydroxide associated with bioactive vehicle - De Souza, Vitor [UNESP]; Zaniboni, Joissi [UNESP]; Escalante-Otárola, Wilfredo [UNESP]; Matsumoto, Mariza [UNESP]; Bighetti, Claudia [UNESP]; Kuga, Milton [UNESP] (Thieme, 2020)
Aim: The aim of this study to evaluate the effects of 10% alpha-tocopherol (10AT) or 20% alpha-tocopherol (20AT) incorporation on biological compatibility, pH, and calcium release of calcium hydroxide (CH) paste associated with 2% chlorhexidine digluconate (CHX). Materials and Methods: Four groups were evaluated: CH, CH-CHX, CH-CHX-10AT, and CH-CHX-20AT. For biological compatibility test, polyethylene tubes containing several pastes were implanted in Wistar rats' subcutaneous tissue (n = 28). After 48 h and 7, 14, and 21 days postimplantation, the specimens were removed and subjected to histologic and histomorphometric analysis. The number of inflammatory cells was evaluated. For pH and calcium release analysis, the pastes were placed individually (n = 10) in plastic tubes and immersed in deionized water. The calcium release and pH changes were evaluated in 24 and 48 h and 7, 14, and 21 days. All data were submitted to Kruskal-Wallis test (α = 0.05). Results: Concerning biological compatibility, all materials shown a similar decidual response (P > 0.05). In the first hours, there was as increase in the number of inflammatory cells, inducing an expressive inflammatory response. After 14 days, inflammation reaction decreased and collagen fiber was organized for the tested pastes (P = 0.05). The pH analysis of the groups maintained the same relationship during the different periods evaluated: the CH and CH-CHX groups showed higher values and were similar to each other (P > 0.05), followed by the CH-CHX-10AT and CH-CHX-20 AT groups. Regarding the amount of calcium ions, in the initial (24 hours) and final (21 days) periods, the groups did not present differences between them (P > 0.05). Conclusion: The 10AT or 20AT, as an antioxidant agent, incorporation to CH and 2% CHX paste negatively affected biological and physicochemical properties.
Keywords: Antioxidants; calcium hydroxide; calcium release; chlorhexidine; subcutaneous tissue